2006
DOI: 10.1039/b603409h
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrins conjugated to DNA as CD reporters of the salt-induced B to Z-DNA transition,

Abstract: The porphyrin chromophore incorporated at the 5'-position of an oligonucleotide allows the simultaneous detection of the B- to Z-DNA transition via the porphyrin Soret band circular dichroism exciton couplet signal around 420 nm and the oligonucleotide CD region below 300 nm, at micromolar concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…35 The UV-ECD spectrum also change its shape substantially, and had a negative couplet, with a maximum at 262(þ), and two minima at 270(À) and 247(À) nm, typical of the B to Z form transition. 11,34 The UV-ECD results correlate with the results on induced CD in the Soret region: both signals reverse the sign of their pattern. This supports our conclusions based on the Soret region ECD study.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…35 The UV-ECD spectrum also change its shape substantially, and had a negative couplet, with a maximum at 262(þ), and two minima at 270(À) and 247(À) nm, typical of the B to Z form transition. 11,34 The UV-ECD results correlate with the results on induced CD in the Soret region: both signals reverse the sign of their pattern. This supports our conclusions based on the Soret region ECD study.…”
supporting
confidence: 56%
“…9 Both UV and Soret regions were used in the ECD studies of bound porphyrin-oligonucleotide conjugates. [10][11][12][13][14] It has been shown that the CD signal of the porphyrin part of the conjugate can serve as a probe of the oligonucleotide conformation and its variation, e.g. the B-Z transitions.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting consequence of the chiral structure of DNA is the induction of chiral effects, such as induced circular dichroism, in achiral molecules interacting with it, a property than can be profitably exploited for the study of small molecule-DNA interactions or to selectively probe DNA conformations, as in the case of the interaction of porphyrins, [21][22][23] acridine, 24 or cyanine dyes with dsDNA or its analogs. 25 The full description of these effects is beyond the scope of this review, which focuses on the chirality of the species interacting with DNA.…”
Section: Chirality and Handedness In The Structure Of Nucleic Acidsmentioning
confidence: 99%
“…3). 22 The attachment of this achiral chromophore to DNA places it into a chiral environment, and allows excitonic coupling between porphyrin moieties giving rise to characteristic CD spectra. These are very sensitive to the porphyrin environment, 23 thus allowing, for example, detection of the change from B to Z form of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…These are very sensitive to the porphyrin environment, 23 thus allowing, for example, detection of the change from B to Z form of DNA. 22 It should be noted that in addition to UV-Vis spectroscopy, CD spectroscopy is a major tool for analysis as it provides very useful information about the DNA's global structure.…”
Section: Introductionmentioning
confidence: 99%